Definition and Validation of a Novel Metric of Erythropoiesis‐Stimulating Agent Response in Hemodialysis Patients. (9th November 2018) - Meaney, Calvin J.; Karas, Spinel; Robinson, Ben; Gaesser, Jamie; Forrest, Alan; Krzyzanski, Wojciech; Panesar, Mandip; Rao, Gauri G.
Abstract: Erythropoiesis‐stimulating agents (eg, epoetin alfa) are the primary treatment for anemia in patients with end‐stage renal disease. Hemoglobin variability in and out of a narrow target range is common and associated with higher morbidity and mortality risk. More robust erythropoiesis‐stimulating agent response metrics are needed to define optimal dosing and their association with clinical outcomes. In this cross‐sectional, single‐center, retrospective study, 49 patients with end‐stage renal disease on hemodialysis were followed over 12 months. To quantify hemoglobin deviations outside the target range (10–12 g/dL), the area under the curve of hemoglobin versus time over a 12‐month period (AUC‐HGB) was calculated using the trapezoidal rule. Patients were categorized into 4 responder groups based on AUC‐HGB quartiles. Comparative analyses of demographic and clinical characteristics between responder groups were performed. Correlations between AUC‐HGB, erythropoietin resistance index, and time within therapeutic range were calculated. There were no significant differences in laboratory and dialysis parameters between responder groups except hemoglobin concentration and epoetin alfa dose. There was a negative correlation between AUC‐HGB and time within therapeutic range ( r = –.92; P < .001) and hemoglobin concentration ( r = –.85; P < .01), indicating internal validity of the metric. There was a positive correlation between AUC‐HGB and erythropoietin resistance index ( r = .70; P < .001) indicating external validity. The poor response group received a higher median epoetin alfa dose (160 U/kg/week) compared to the excellent response group (68.8 U/kg/week; P < .001) with a similar number of dose changes between the groups. AUC‐HGB is a valid marker of epoetin alfa response and should be considered in future analyses of larger populations.